General patterns of memory development of younger school age pupils (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the general characteristics of the memory of younger school-age pupils. It is revealed the classification of memory types appearing in junior pupils. The strategy of mnemonics use in work with younger school-age pupils is determined.
Keywords: younger school age pupils; mnemonics; memory